Novel Method for Improving the Utilization of Corn Dried Distillers Grains with Solubles in Broiler Diets - Shalash, S.M.M.; Ali, M.N.; Sayed, M.A.M.; El-Gabry, Hoda E.; Shabaan, M. (International Journal of Poultry Science, 2009)
An experiment was conducted with broiler chicks to study the possibility of improving the utilization of Dried Distillers Grains with Solubles (DDGS) in broiler diets. A total number of 150 day-old broiler chicks were randomly assigned to five groups received, diet containing 12% corn Dried Distillers Grains with Solubles (DDGS diet) without or with enzyme preparation (E), radish root extract (RRE, as source of peroxidase enzyme ) or E plus RRE, in addition to the control diet .The addition of RRE improved numerically Body Weight (BW) at 28 days and significantly at 42 days by 3.42 and 3.11%, respectively compared to birds fed DDGS diet alone. Enzyme preparation failed to improve performance for broiler fed DDGS diet. While using DDGS diet significantly decreased plasma antioxidants capacity by 56.11% compared to control birds, addition of RRE significantly increased it by 515% compared to the birds fed DDGS diet alone. There were insignificant differences between experimental treatments in plasma cholesterol, lipids or creatinine content. The addition of RRE increased plasma phosphorus by 65.93% compared to the birds fed DDGS diet alone while the later decreased it by 6.22% compared to control diet. The control birds recorded significantly higher values of plasma uric acid compared to other treatments. It was concluded that using RRE as a source of peroxidase enzyme is a suitable feed additive for improving the utilization of DDGS.